Multimodal Analysis on the House Brochure - Antari, Irna; Nur Ali, Ahmad Jum'a Khatib (International Journal of English and Applied Linguistics (IJEAL), 2024)
This study aims at describing verbal and visual elements in house brochure of Graha Utama Tobo. The verbal and visual elements are analysed by using Cheong?s (2004) generic structure. The researcher used descriptive research method. The data in this research were verbal and non-verbal texts found in house brochure of Graha Utama Trobo. The brochure was downloaded from facebook account that is chosen randomly. The result of the study reveals that the brochures have all generic structure which is lead, display, emblem (verbal), announcement, enhancer, emblem (visual), tag, and call-and-visit information. The finding house brochure fully supports Cheong?s (2004) theory. The verbal and visual elements support each other and cohere to convey a message to the reader. The message conveyed to readers become more persuasive, and it arouses their interest to use the tour and travel company service.